1997
DOI: 10.1007/s002880050429
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduction of jets and heavy flavors at future polarized ep -colliders

Abstract: We study photoproduction of jets and heavy flavors in a polarized collider mode of HERA and in polarized ep collisions at √ S ≈ 30 GeV. We examine the sensitivity of the cross sections and their asymmetries to the proton's polarized gluon distribution and to the completely unknown parton distributions of longitudinally polarized photons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…In the course of the parton model analysis, we also obtain the polarized parton distributions [2,45] of the longitudinally polarized photon, for the case of virtual photon, which will be discussed elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of the parton model analysis, we also obtain the polarized parton distributions [2,45] of the longitudinally polarized photon, for the case of virtual photon, which will be discussed elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…The information on the spin structure of the photon would be provided by the resolved photon process in polarized electron and proton collision in the polarized version of HERA [1,2]. More directly, the spin-dependent structure function of photon g γ 1 can be measured by the polarized e + e − collision in the future linear colliders (Fig.1).…”
Section: Introductionmentioning
confidence: 99%
“…At the Born level, (1.1) has been studied long ago [3,4]. However, the importance of knowing the next-to-leading order corrections (NLOC) cannot be overemphasized.…”
Section: Introductionmentioning
confidence: 99%
“…Since the parton content of polarized photons is completely unknown so far, one has to impose some realistic models [20] to estimate this contribution. In [7] it was shown that even for rather large photonic densities this 'background' should also be very small in the 'COMPASS region'. Moreover, the unknown precise value of the charm quark mass m leads to shifts in ∆σ γp and A c γp of about 30% when m is varied by 0.…”
mentioning
confidence: 99%
“…Heavy quark (Q = c, b) production is generally considered to be one of the best options to pin down ∆g since in leading order (LO) only the photongluon fusion (PGF) process [6] γ g → QQ (1) contributes (an arrow denotes a longitudinally polarized particle). All studies of this process so far [5,6,7,8] were limited to LO estimates which, however, are known to be notoriously unreliable due to, e.g., their strong factorization/renormalization scale dependence. In addition, the already available unpolarized NLO corrections [9,10] turn out to be sizeable in certain kinematical regions and the 'clean picture' of Eq.…”
mentioning
confidence: 99%